Kegiatan Perbaikan dan Pengecatan Tembok di Lingkungan Madrasah Diniyah Aljauharotunnaqiyyah - Bait Dwi Christianto; Surachman Surachman; Umi Prasasti; Dimas Fajrian; Mauliya Fitriani (Karya Nyata : Jurnal Pengabdian kepada Masyarakat, 2024)
School educational institutions are institutions that provide teaching and learning processes that must be supported by good facilities and infrastructure. Not only that, you also need a sense of security and comfort in the classroom so that it is hoped that there will be a feeling of enthusiasm for learning. The aim of Community Service (PKM) in the social, cultural and environmental fields by the Student Work Lecture (KKM) group 40 of Cikerai Subdistrict is to increase students' enthusiasm for learning through repairing and painting classroom walls both inside and outside the classroom. The method used is the ABCD (Asset Based Communities Development) approach which emphasizes an inventory of existing assets in the community. The PKM results show that there are changes in the atmosphere produced before and after painting, this is expected to make students enthusiastic and feel at home studying at the school. Long-term efforts need to be made to maintain and preserve the school environment so that the program becomes even more perfect.